Pengaruh Harga, Cita Rasa, dan Lokasi terhadap Minat Beli Konsumen Elo Pia Kediri - Fitria Kurniasari; Aprilia Dian Evasari; Beny Mahyudi Saputra (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aimed to better understand how factors like price, taste, and location affect how much consumers want to buy Elo Pia Kediri products. The research used a quantitative method because it helps collect objective and measurable information that can be analyzed using statistics to make clear conclusions. The data came from two main places: primary and secondary sources. Primary data was gathered directly from consumers through questionnaires that asked about price, taste, location, and how much they wanted to buy the product. Secondary data was collected from books, articles, and other documents related to the topic. The study included all consumers who had bought Elo Pia Kediri products. However, since the total number of people wasn’t known and was quite large, the researcher selected a representative group. The sample size was 96 people. The method used to choose participants was accidental sampling, which means people were selected randomly or by chance as they were met at the research location and agreed to take part. The results showed that price has a big effect on how much consumers want to buy the product. This means the prices set by Elo Pia Kediri match what consumers can afford and what they think is fair, which helps them decide to buy. When prices are seen as fair, affordable, and matching the quality of the product, it encourages people to make purchases. Taste also strongly influences buying interest. When a product has a tasty and unique flavor that fits what people like, it makes them interested in buying it. Taste is an emotional factor that affects how happy consumers are with the product and makes them want to buy it again. Location also plays a big role in how much people want to buy. A location that is easy to reach and close to where people usually go out makes it easier for them to buy Elo Pia Kediri products. The F test showed that together, price, taste, and location all have a significant impact on how much consumers want to buy the product.